Anion-regulated Fe (II) spin crossover magnetic material as well as preparation method and application thereof

Through anion-regulated Fe(II) spin cross magnetic material, the hydrogen bond difference between anion and organic ligand is used to achieve fine regulation of the properties of autorotation, solving the problem of difficult regulation in the prior art and improving the problem of improvement. The performance stability of the material has a wide range of application prospects.

CN119431224APending Publication Date: 2025-02-14QUZHOU RES INST OF ZHEJIANG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411358868.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively regulate the rotational properties of spin-cross magnetic materials, especially on the macroscopic scale, the rotational conversion behavior is affected by the synergistic action between molecules, which makes it difficult to regulate.

Method used

Fe(II) spin cross magnetic material regulated by anion, its chemical structure is [Fe(bamp)2]·A2·nS, through different anions (Cl-, Br-, I-) and organic ligand 2, The hydrogen bond difference between 6-bis(aminomethyl)pyridine achieves fine regulation of autorotating properties.

Benefits of technology

The finely regulated self-rotation degeneration properties of different anions are achieved, and the performance stability of spin-crossing materials is improved, and it has potential application value in the fields of crystallography, molecular switching and information storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431224A_ABST
    Figure CN119431224A_ABST
Patent Text Reader

Abstract

The invention discloses an anion-regulated Fe (II) spin crossover magnetic material as well as a preparation method and application thereof. Compared with solvothermal synthesis, solvent diffusion and other synthesis methods, the preparation method provided by the invention has the advantages of simple reaction conditions, low cost / high yield, easy implementation and the like, the used organic ligand 2, 6-bis (aminomethyl) pyridine has abundant electron donating amino groups and is easy to generate abundant hydrogen bonds, and meanwhile, different anions (Cl <->, Br <-> and I <->) and the ligand main body 2, 6-bis (aminomethyl) pyridine are in one-to-one correspondence. According to the present invention, with the difference of hydrogen bonds between 2, 6-bis (aminomethyl) pyridine, the regulation of different anions (Cl <->, Br <-> and I <->) on the temperature and the rate of the spin transition system is achieved, the new idea is provided for the precise regulation of the spin crossover material, and the synthesized Fe (II) spin crossover magnetic material has characteristics of simple structure, stable performance, and easy industrial production. The potential application value is realized in the fields of crystallography, molecular switches and information storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of molecular-based magnetic materials and crystal materials, and specifically relates to an anion-regulated Fe(II) spin-crossover magnetic material and a preparation method and application thereof. Background Art

[0002] Spin-crossover (SCO) complexes are classic molecular magnets with magnetic bistability and are a class of molecular-based magnetic functional materials that have attracted much attention in recent years. Under external stimuli (such as temperature, magnetic field, light, electric field, pressure) or chemical (such as pH, solvent, gas adsorption) perturbations, the 3d ligands in the appropriate ligand field can be directly connected to the magnetic field. 4~7 The electron configuration of transition metal central ions undergoes a reversible change from high spin (HS) to low spin (LS), resulting in a significant change in magnetic signals, accompanied by changes in physical properties such as dielectric constant, volume, and color. This shows promising application prospects in the fields of molecular switches, sensors, and information storage. However, how to controllably regulate the properties of spin conversion has always been a severe challenge in this field, because spin conversion behavior at the macroscopic scale depends not only on the intrinsic properties of individual molecules, but also on the synergy between molecules.

[0003] π-π stacking interactions and hydrogen bonding play an important role in the spin conversion behavior, especially π-π interactions can lead to strong synergistic effects. In compounds without π-π stacking structures, hydrogen bonding is crucial. [Fe(2-pic) 3 ]·A 2 Solv (2-pic refers to the organic ligand 2-methylaminopyridine, A represents anion, and Solv represents solvent molecule) is a classic system for studying the effect of hydrogen bonding interactions on SCO behavior in detail. However, designing and controlling these weak interactions remains a major challenge. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of the embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide an anion-regulated Fe(II) spin-crossover magnetic material, wherein: the chemical structural formula of the Fe(II) spin-crossover magnetic material is [Fe(bamp) 2 ]·A 2 nS;

[0007] In the formula, bamp represents 2,6-bis(aminomethyl)pyridine, and A represents an anion selected from Cl - ,Br - , I - One of them, S means H 2 O, n ranges from 0 to 2;

[0008] The crystal structure of the Fe(II) spin-crossed magnetic material is monoclinic, and the space group is C2 / c or P2 1 / c, Fe-N bond length range is or

[0009] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing the anion-regulated Fe(II) spin-crossover magnetic material.

[0010] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0011] The preparation method is carried out under anaerobic conditions.

[0012] 2,6-Bis(aminomethyl)pyridine is dissolved in an oxygen-free solvent to obtain solution Ⅰ;

[0013] The divalent iron salt is dissolved in an oxygen-free solvent to obtain solution II;

[0014] Solution II is added to solution I, and the mixture is stirred, filtered, and evaporated in sequence. The precipitated red crystals are the anion-regulated Fe(II) spin-crossed magnetic materials.

[0015] As a preferred embodiment of the method for preparing the anion-regulated Fe(II) spin-crossover magnetic material of the present invention, the oxygen-free solvent is treated with nitrogen and is obtained by mixing one or two solvents selected from deionized water, acetonitrile or methanol.

[0016] As a preferred embodiment of the method for preparing the anion-regulated Fe(II) spin-crossover magnetic material of the present invention, when the oxygen-free solvent is obtained by mixing two solvents, the mixing volume ratio of the two solvents is 1:0.25-4.

[0017] As a preferred solution of the method for preparing the anion-regulated Fe(II) spin-crossover magnetic material of the present invention, the nitrogen treatment time is 12 to 24 hours.

[0018] As a preferred embodiment of the method for preparing the anion-regulated Fe(II) spin-crossover magnetic material of the present invention, the concentration of the divalent iron salt in the solution II is 0.1-0.3 mol / L.

[0019] As a preferred embodiment of the method for preparing the anion-regulated Fe(II) spin-crossover magnetic material of the present invention, the molar ratio of the 2,6-bis(aminomethyl)pyridine to the divalent iron salt is 2:1 to 1.2.

[0020] As a preferred embodiment of the method for preparing the anion-regulated Fe(II) spin-crossover magnetic material of the present invention, the divalent iron salt comprises one or more of ferrous chloride, ferrous bromide and ferrous iodide.

[0021] As a preferred solution of the method for preparing the anion-regulated Fe(II) spin-crossover magnetic material of the present invention, the stirring time is 5 to 10 minutes.

[0022] Another object of the present invention is to overcome the deficiencies in the prior art and provide the application of the anion-regulated Fe(II) spin-crossover magnetic material in ultra-high density information storage and molecular switches.

[0023] Beneficial effects of the present invention:

[0024] (1) The organic ligand 2,6-bis(aminomethyl)pyridine in the present invention has abundant electron-donating amino groups, which are easy to generate abundant hydrogen bonds. - Br - ,I - The difference in hydrogen bonding between the anion and the ligand 2,6-bis(aminomethyl)pyridine enables fine tuning of the anion's spin transition properties.

[0025] (2) Compared with other synthesis methods such as solvent thermal synthesis and solvent diffusion, the preparation method of Fe(II) spin crossover magnetic material in the present invention has the advantages of simple reaction conditions, low cost / high yield, and easy implementation.

[0026] (3) The present invention uses different counter anions to obtain three crystalline spin crossover materials, achieving different anions (Cl - Br - ,I -) provides a new idea for the precise control of spin-crossover materials by regulating the temperature and rate of the spin conversion system. The synthesized Fe(II) spin-crossover magnetic material has a simple structure and stable performance, and has potential application value in the fields of crystallography, molecular switches and information storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0028] Figure 1 [Fe(bamp) in Example 1 of the present invention 2 ]·Cl 2 ·2H 2 Crystal structure and stacking diagram of O.

[0029] Figure 2 [Fe(bamp) in Example 3 of the present invention 2 ]·I 2 Crystal structure and stacking diagram.

[0030] Figure 3 [Fe(bamp) in Example 1 of the present invention 2 ]·Cl 2 ·2H 2 Powder X-ray diffraction pattern of O.

[0031] Figure 4 [Fe(bamp) in Example 2 of the present invention 2 ]·Br 2 ·2H 2 Powder X-ray diffraction pattern of O.

[0032] Figure 5 [Fe(bamp) in Example 3 of the present invention 2 ]·I 2 Powder X-ray diffraction pattern of .

[0033] Figure 6 [Fe(bamp) in Examples 1-3 of the present invention 2 ]·Cl 2 ·2H 2 O, [Fe(bamp) 2 ]·Br 2 ·2H 2 O and [Fe(bamp) 2 ]·I 2Temperature-dependent magnetic susceptibility curve. DETAILED DESCRIPTION

[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0035] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0036] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0037] The reagents used in the present invention are all commercially available and analytically pure. Except for the solvent which is deoxygenated, other reagents are not further purified before use.

[0038] Example 1

[0039] This embodiment provides a divalent iron complex material [Fe(bamp) 2 ]·Cl 2 ·2H 2 Preparation method of O:

[0040] Methanol and water were placed in Schlenk bottles respectively, and nitrogen was bubbled into the solvent through a gas tube for 24 hours to obtain an oxygen-free solvent;

[0041] In a glove box, 0.4 mmol of organic ligand bamp (2,6-bis(aminomethyl)pyridine) was added to 2 mL of oxygen-free methanol solvent and dissolved by stirring at room temperature;

[0042] Then, in a glove box, 0.2 mmol of ferrous chloride was added to 2 mL of water and dissolved by stirring at room temperature;

[0043] The ferrous chloride aqueous solution obtained above was slowly added to the methanol solution of the organic ligand and stirred at room temperature for 10 minutes. Filtered and allowed to evaporate, dark red block crystals suitable for X-ray diffraction were precipitated after two weeks, which was the divalent iron complex [Fe(bamp) 2 ]·Cl 2 ·2H 2 O.

[0044] [Fe(bamp)2 ]·Cl 2 ·2H 2 The O yield was 52%.

[0045] Example 2

[0046] This embodiment provides a divalent iron complex material [Fe(bamp) 2 ]·Br 2 ·2H 2 Preparation method of O:

[0047] Water and acetonitrile were placed in Schlenk bottles respectively, and nitrogen was bubbled into the solvent through a gas tube for 24 hours to obtain an oxygen-free solvent.

[0048] In a glove box, 0.4 mmol of organic ligand bamp (2,6-bis(aminomethyl)pyridine) was added to 2 mL of a mixed solvent of acetonitrile and water (volume ratio 1:1) and stirred at room temperature to dissolve.

[0049] Then, in a glove box, 0.2 mmol of ferrous bromide was added to 2 mL of water and dissolved by stirring at room temperature.

[0050] The ferrous bromide aqueous solution obtained above was slowly added to the mixed solution of organic ligands and stirred at room temperature for 10 minutes. Filtered and allowed to evaporate, red block crystals suitable for X-ray diffraction were precipitated after two weeks, which was the divalent iron complex [Fe(bamp) 2 ]·Br 2 ·2H 2 O.

[0051] [Fe(bamp) 2 ]·Br 2 ·2H 2 The O yield was 58%.

[0052] Example 3

[0053] This embodiment provides a divalent iron complex material [Fe(bamp) 2 ]·I 2 Preparation method:

[0054] Methanol and water were placed in Schlenk bottles respectively, and nitrogen was bubbled into the solvent through a gas tube for 24 hours to obtain an oxygen-free solvent.

[0055] In a glove box, 0.4 mmol of organic ligand bamp (2,6-bis(aminomethyl)pyridine) was added to 2 mL of methanol solvent and dissolved by stirring at room temperature.

[0056] Then, in a glove box, 0.2 mmol of ferrous iodide was added to 2 mL of water and dissolved by stirring at room temperature.

[0057] The ferrous iodide aqueous solution obtained above was slowly added to the methanol solution of the organic ligand and stirred at room temperature for 10 minutes. Filtered and allowed to evaporate, red block crystals suitable for X-ray diffraction were precipitated after two weeks, which was the divalent iron complex [Fe(bamp) 2 ]·I 2 .

[0058] Iron (bamp) 2 ]·I 2 The yield was 63%.

[0059] The specific characterization of the divalent iron complexes of different anions prepared in Examples 1-3 is as follows:

[0060] (1) Crystal structure determination. The instrument used was the Apex Duo single crystal diffractometer from Bruker, and the radiation source was Mo-Kα radiation from a graphite monochromator. The single crystal analysis data are shown in Table 1.

[0061] Table 1 Complexes [Fe(bamp) 2 ] system crystal data and structure refinement parameters

[0062]

[0063]

[0064] Figure 1 and Figure 2 There are three complexes [Fe(bamp) 2 ] system. Combining Table 1 and Figure 1 , 2 The results show that the three complexes with different anions all belong to the monoclinic system, and the complexes [Fe(bamp) 2 ]·Cl 2 ·2H 2 O and [Fe(bamp) 2 ]·Br 2 ·2H 2 O has the same molecular structure. In the complex [Fe(bamp) 2 ]·Cl 2 ·2H 2 The smallest asymmetric unit of O contains 1.5 [Fe(bamp) 2 ] 2+ Cationic center, three Cl -anion, and 2.5 free water molecules. The Fe(II) metal center is coordinated by two organic ligands to form an octahedral structure coordinated by six nitrogen atoms.

[0065] The octahedral configuration can be obtained by calculation using SHAPE software, as shown in Table 2.

[0066] Table 2Fe 2+ Some calculated data of ion coordination configuration

[0067]

[0068]

[0069] Note: HP is hexagon, PPY is pentagonal pyramid, OC is octahedron, TPR is triangular prism, and JPPY is Johnson pentagonal pyramid.

[0070] From Table 2, we can see that the Fe1-N coordination bond length is The Fe2-N coordination bond length is These bond lengths indicate the spin states of the Fe(II) metal center, with Fe1 being in a low-spin state and Fe2 being in a high-spin state at 153K.

[0071] Complex [Fe(bamp) 2 ]The coordination bond lengths of the metal centers in the system are shown in Table 3.

[0072] Table 3 Complexes [Fe(bamp) 2 ]The coordination bond length of the metal center in the system

[0073]

[0074] It can be seen from Table 3 that the complex [Fe(bamp) 2 ]·I 2 Belongs to P2 1 / c space group, the smallest asymmetric unit contains only one [Fe(bamp) 2 ] 2+ The cation center and two I - Anion. Fe1-N coordination bond length is This indicates that the Fe(II) metal center is in a high-spin state at this temperature.

[0075] (2) Powder X-ray diffraction determination of phase purity

[0076] The phase purity of the crystalline product obtained in this example was characterized using a Bruker D8 Advance powder X-ray diffractometer, and the theoretical data was obtained by simulating the single crystal structure data using Mercury software.

[0077] Figures 3 to 5 The X-ray diffraction diagrams of the crystal powders of Examples 1-3 show that the experimental values ​​of the diffraction peaks of the three complexes are very consistent with the diffraction peaks simulated by the single crystal structure, indicating that the material has a high phase purity, which provides a guarantee for its application in molecular-based magnetic materials.

[0078] (3) Magnetic properties characterization

[0079] The magnetic measurement adopts the superconducting quantum interference device Quantum Design MPMS SQUID VSM magnetic measurement system. The test temperature of DC magnetic susceptibility is 2~300K (or 350K) and the magnetic field is 1000Oe.

[0080] Test results such as Figure 6 As shown. It can be seen that at 300K, the anion is Cl - Br - and I - The three ferrous iron compounds have M The T values ​​are 3.11, 3.19 and 3.14 cm respectively 3 mol -1 K, which is close to the high spin theoretical value of 3 cm for hexacoordinated divalent iron (S = 2). 3 mol -1 K.

[0081] As the temperature is cooled from 350K to 100K, the complex [Fe(bamp) 2 ]·Cl 2 ·2H 2 O's χ M The T value gradually decreases to 1.02cm 3 mol -1 K, achieving partial spin transition behavior with a transition temperature of 210 K. This partial spin transition phenomenon is consistent with the coordination bond length in crystal tests, that is, one-third of the Fe(II) metal centers are in a high spin state.

[0082] As the temperature is cooled from 300K to 2K, the complex [Fe(bamp) 2 ]·Br 2 ·2H 2 The MT value of O gradually decreased to 0.06 cm 3 mol -1K, which is consistent with the transition from high spin state (S=2) to low spin state (S=0). The complex has a gradual spin crossover property, and its spin transition temperature is 156K.

[0083] As the temperature is cooled from 300K to 50K, the complex [Fe(bamp) 2 ]·I 2 χ M The T value dropped to 2.93cm 3 mol -1 K, almost unchanged, indicating that the Fe(II) metal center is always in a high spin state. When the temperature is lower than 50K, the value of the magnetic susceptibility continues to decrease, which is due to the influence of high spin zero field splitting rather than further spin transition. Therefore, the complex does not have spin crossover properties.

[0084] Example 4

[0085] This embodiment provides a divalent iron complex material [Fe(bamp) 2 ]·Br 2 ·2H 2 Preparation method of O:

[0086] Water and acetonitrile were placed in Schlenk bottles respectively, and nitrogen was bubbled into the solvent through a gas tube for 24 hours to obtain an oxygen-free solvent.

[0087] In a glove box, 0.4 mmol of organic ligand bamp (2,6-bis(aminomethyl)pyridine) was added to 2 mL of a mixed solvent of acetonitrile and water (volume ratio 1:1) and stirred at room temperature to dissolve.

[0088] Then, in a glove box, 0.2 mmol of ferrous chloride and 0.4 mmol of sodium bromide were added to 2 mL of water and dissolved by stirring at room temperature.

[0089] The mixed ferrous aqueous solution obtained above was slowly added to the methanol solution of the organic ligand and stirred at room temperature for 10 minutes. Filtered and allowed to evaporate, red block crystals suitable for X-ray diffraction were precipitated after two weeks, which was the divalent iron complex [Fe(bamp) 2 ]·Br 2 ·2H 2 O.

[0090] Iron (bamp) 2 ]·Br 2 ·2H 2 The yield of O is 35%. Although [Fe(bamp) 2 ]·Br 2 ·2H 2O, but the yield is significantly lower than that of Example 2.

[0091] Example 5

[0092] This embodiment provides a divalent iron complex material [Fe(bamp) 2 ]·I 2 Preparation method:

[0093] Methanol and water were placed in Schlenk bottles respectively, and nitrogen was bubbled into the solvent through a gas tube for 24 hours to obtain an oxygen-free solvent.

[0094] In a glove box, 0.4 mmol of organic ligand bamp (2,6-bis(aminomethyl)pyridine) was added to 2 mL of methanol solvent and dissolved by stirring at room temperature.

[0095] Then, in a glove box, 0.2 mmol of ferrous chloride and 0.4 mmol of sodium iodide were added to 2 mL of water and dissolved by stirring at room temperature.

[0096] The mixed ferrous aqueous solution obtained above was slowly added to the methanol solution of the organic ligand and stirred at room temperature for 10 minutes. Filtered and allowed to evaporate, red block crystals suitable for X-ray diffraction were precipitated after two weeks, which was the divalent iron complex [Fe(bamp) 2 ]·I 2 .

[0097] Iron (bamp) 2 ]·I 2 The yield was 41%, which was significantly lower than that in Example 3.

[0098] Comparative Example 1

[0099] The difference between this comparative example and Example 1 is that only methanol is selected as the solvent, and other operations are the same as those in Example 1.

[0100] No complex crystalline material was produced.

[0101] Comparative Example 2

[0102] The difference between this comparative example and Example 1 is that nitrogen is not introduced into methanol and water for deoxygenation treatment, and other operations are the same as those in Example 1.

[0103] No complex crystalline material was produced.

[0104] Comparative Example 3

[0105] The difference between this comparative example and Example 3 is that only methanol is selected as the solvent, and other operations are the same as Example 3.

[0106] No complex crystalline material was produced.

[0107] Comparative Example 4

[0108] The difference between this comparative example and Example 1 is that the amount of ferrous chloride added is adjusted to 0.1 mmol, that is, the molar ratio of bamp to ferrous chloride is 4:1, and the yield of the synthesized complex crystal material is extremely low, only 3%.

[0109] Comparative Example 5

[0110] The difference between this comparative example and Example 1 is that the amount of ferrous chloride added is adjusted to 0.4 mmol, that is, the molar ratio of bamp to ferrous chloride is 0.5:1, and the yield of the synthesized complex crystal material is extremely low, close to 0.

[0111] In summary, the organic ligand 2,6-bis(aminomethyl)pyridine in the present invention has abundant electron-donating amino groups, which are easy to generate abundant hydrogen bonds. - Br - ,I - ) and the coordination host 2,6-bis(aminomethyl)pyridine realize the fine control of the spin transition properties of the anion. Compared with the synthesis methods such as solvent thermal synthesis and solvent diffusion, the preparation method of Fe(II) spin crossover magnetic material has the advantages of simple reaction conditions, low cost / high yield, and easy implementation. The present invention uses different counter anions to obtain three crystalline spin crossover materials, realizing different anions (Cl - Br - ,I - ) provides a new idea for the precise control of spin-crossover materials by regulating the temperature and rate of the spin conversion system. The synthesized Fe(II) spin-crossover magnetic material has a simple structure and stable performance, and has potential application value in the fields of crystallography, molecular switches and information storage.

[0112] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. An anion-regulated Fe(II) spin crossover magnetic material, characterized in that: The chemical structural formula of the Fe(II) spin crossover magnetic material is [Fe(bamp)2]·A2·nS; In the formula, bamp represents 2,6-bis(aminomethyl)pyridine, and A represents an anion selected from Cl - ,Br - , I - One of the following, S represents H2O, and n is 0 to 2; The crystal structure of the Fe(II) spin-crossed magnetic material is monoclinic, the space group is C2 / c or P21 / c, and the Fe-N bond length ranges from or 2. The method for preparing anion-regulated Fe(II) spin crossover magnetic material according to claim 1, characterized in that: The preparation method is carried out under anaerobic conditions and comprises: 2,6-Bis(aminomethyl)pyridine is dissolved in an oxygen-free solvent to obtain solution Ⅰ; The divalent iron salt is dissolved in an oxygen-free solvent to obtain solution II; Solution II is added to solution I, and the mixture is stirred, filtered, and evaporated in sequence. The precipitated red crystals are the anion-regulated Fe(II) spin-crossed magnetic materials.

3. The method for preparing anion-regulated Fe(II) spin crossover magnetic material according to claim 2, characterized in that: The oxygen-free solvent is treated with nitrogen and is obtained by mixing one or two solvents selected from deionized water, acetonitrile or methanol.

4. The method for preparing anion-regulated Fe(II) spin crossover magnetic material according to claim 3, characterized in that: When the oxygen-free solvent is obtained by mixing two solvents, the mixing volume ratio of the two solvents is 1:0.25-4.

5. The method for preparing anion-regulated Fe(II) spin crossover magnetic material according to claim 3, characterized in that: The nitrogen treatment time is 12 to 24 hours.

6. The method for preparing anion-regulated Fe(II) spin-crossover magnetic material according to claim 2, characterized in that: The concentration of the divalent iron salt in the solution II is 0.1-0.3 mol / L.

7. The method for preparing anion-regulated Fe(II) spin-crossover magnetic material according to claim 2, characterized in that: The molar ratio of the 2,6-bis(aminomethyl)pyridine to the divalent iron salt is 2:1-1.

2.

8. The method for preparing anion-regulated Fe(II) spin-crossover magnetic material according to claim 7, characterized in that: The divalent iron salt includes one or more of ferrous chloride, ferrous bromide and ferrous iodide.

9. The method for preparing anion-regulated Fe(II) spin-crossover magnetic material according to claim 2, characterized in that: The stirring time is 5 to 10 minutes.

10. Application of the anion-regulated Fe(II) spin crossover magnetic material as claimed in claim 1 in ultra-high density information storage and molecular switches.

Citation Information

Patent Citations

  • Spin crossover Fe (II) complex magnetic porous crystal material as well as preparation method and application thereof

    CN116769182A